2019
DOI: 10.1016/j.csbj.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-based Pharmacophore Modeling, Virtual Screening and Molecular Docking Studies for Discovery of Potential Topoisomerase I Inhibitors

Abstract: Camptothecin (CPT), a natural product and its synthetic derivatives exert potent anticancer activity by selectively targeting DNA Topoisomerase I (Top1) enzyme. CPT and its clinically approved derivatives are used as Top1 poisons for cancer therapy suffer from many limitations related to stability and toxicity. In order to envisage structurally diverse novel chemical entity as Top1 poison with better efficacy, Ligand-based-pharmacophore model was developed using 3D QSAR pharmacophore generation ( H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 36 publications
1
84
0
Order By: Relevance
“…Topoisomerase I (PDB ID: 1T8I) is complex with the standard pre-bonded top I poison camptothecin as a co-crystal in a planar geometry with the important residues Arg-364, Asp-533 and Thr-718 in active site of 1T8I. [45]. In our in-silico molecular docking studies of quinolines and benzofurans with target receptor mTOR [31] revealed that Q4, Q9 and Q10 possess significant binding interaction with more number of hydrogen bond formation as compared to all the benzofurans.…”
Section: Discussionmentioning
confidence: 99%
“…Topoisomerase I (PDB ID: 1T8I) is complex with the standard pre-bonded top I poison camptothecin as a co-crystal in a planar geometry with the important residues Arg-364, Asp-533 and Thr-718 in active site of 1T8I. [45]. In our in-silico molecular docking studies of quinolines and benzofurans with target receptor mTOR [31] revealed that Q4, Q9 and Q10 possess significant binding interaction with more number of hydrogen bond formation as compared to all the benzofurans.…”
Section: Discussionmentioning
confidence: 99%
“…Discovery Studio was used to convert it into a 3D form with energy minimization, optimized with the MMFF force eld, and constructed up to 255 different conformations for each compound in the energy range of 20 kcal mol -1 . These conformations were used to construct pharmacophores and to predict the activity of new discovered compounds [21]. Twenty-one compounds were randomly selected as training sets ( Figure 2) and the rest as test sets.…”
Section: Compound Preparationsmentioning
confidence: 99%
“…Discovery Studio was used to convert it into a 3D form with energy minimization, optimized with the MMFF force eld, and constructed up to 255 different conformations for each compound in the energy range of 20 kcal mol − 1 . These conformations were used to construct pharmacophores and to predict the activity of new discovered compounds [21]. Twenty-one compounds were randomly selected as training sets (Fig.…”
Section: Compound Preparationsmentioning
confidence: 99%